Procedimentos para o processo de planejamento da construção : estudo de caso, São Carlos, Estado de São Paulo. - Moraes, Rosa Maria de Mattos (2007)
The competitiveness at the civil construction companies segment depends on the management efficient of its planning and execution control systems. The construction planning through more efficient models it's leaving of being an ideal to be a reality in some companies, as a strategy for quality improvement of its products and the competitiveness increase in their market. This research is focused on the building planning system improvement, with emphasis in building programming and control, through the use of computational tools, aiming, in special, the segment of multi-story buildings. The objective is to present systematic and usual procedures in the planning process of the construction. The implementation of the planning process is demonstrated through a case study, which considers since the stage of building program conception up to the execution control, performed through the building follow-up. The result of this research is the presentation of an easily implemented planning process for the segment of multi-story building companies, which generate quick information to support decisions.